Lethrus (Lethrus) thracicus (Coleoptera: Geotrupidae), a new species from the European part of Turkey - Král, David; Hillert, Oliver; Drožová, Dana; Šípek, Petr (Zootaxa, 2018)
Lethrus (Lethrus) thracicus Král & Hillert, new species, from Thrace, north-western Turkey is described. The new species is compared with the morphologically similar species L. (L.) apterus (Laxmann, 1770), L. (L.) ares Král, Rejsek & Schneider, 2001 and L. (L.) schneideri Král & Hillert, 2013. Relevant diagnostic male characters (shape of mandibles, ventral mandible processes, pronotum and parameres) are illustrated. The name Lethrus subaeneus Fairmaire, 1866 is considered a nomen nudum.